Case report: Tenecteplase for acute ischemic stroke after heparin reversal - Desai, Manali; Fahad, Ameen; Anderson, Kristi; Erdman, Michael; Silliman, Scott (Frontiers in Stroke, 2024)
Intravenous thrombolysis can be administered to appropriate patients with suspected acute ischemic strokes who are on intravenous heparin infusions after its rapid reversal with protamine sulfate. Several case reports suggest the safety of tissue-type plasminogen activator, or alteplase, in these scenarios. Noting the increasing preferential use of tenecteplase over alteplase for intravenous thrombolysis of acute ischemic stroke, the safe and efficacious use of tenecteplase following heparin reversal has not been demonstrated in the literature. Our case demonstrates successful use of intravenous tenecteplase in a patient who was anticoagulated with therapeutic heparin. The patient had no hemorrhagic complications and had an excellent neurological outcome.